A New Representation of the Extended Fermi-Dirac and Bose-Einstein Functions - Asifa Tassaddiq (International Journal of Mathematics And its Applications, 2017)
In [22] the authors discuss the extended Fermi-Dirac and Bose-Einstein functions. In this paper, we discuss a new representation of these functions as a series of complex delta functions. This leads to a similar representation for the Hurwitz and Riemann zeta functions.